Constraints to participation in organised competitive sport in university among Nanyang Technological University (NTU) students in Singapore - Yeo, Zhi Hui (2017)
This research aims to examine the constraints that prevent Nanyang Technological University (NTU) students who have previously participated in organised competitive sports in schools from continuing them in university. Tertiary institutions like universities are vital environments that provide excellent opportunities for helping young adults gain the physiological, psychological and social benefits of participating in organised sport. Such participation allows and encourages participants to practice and compete in an organised and controlled environment which fosters teamwork, cooperation and loyalty, as well as shaping future societal principles and norms. Intrapersonal, interpersonal and structural constraints have been identified as the three primary sources of constraints. Online survey was conducted through Google Forms and data was collected using Microsoft Excel 2010 for Windows. Data from 25 females and 25 males were analysed using Statistical Package for the Social Sciences (SPSS) software. Results showed that there was a significant difference across genders in personal/psychological factors and facilities. There was also a significant difference between residing on campus residences in time and scheduling. Structural constraints were found to be the most significant in influencing participation, followed by interpersonal then intrapersonal constraints. This study will be useful to university policy makers and related personnel in understanding the constraints behind the discontinuation of competitive sports, helping them to make future decisions to encourage and further support the continuation of sport participation in the university.